FRONEMAN, Gabriël Francois van Lingen Inventory of documents - FRONEMAN, Gabriël Francois van Lingen (ARCA, 2018)
Private papers of G.F.van L. Froneman, National Party MPC Frankfort [1943-1953], MP Frankfort-Heilbron [1953-1958], Heilbron [1958-1969], Administrator of the Free State [1969-1974]
COVERAGE 1939-1974; 1016 Files; 24,22 Metres. AUDIO CASSETTES IN ARCA COLLECTION = 2
Keywords: FRONEMAN, Gabriël Francois van Lingen; Inventories; Politicians; National Party